2022
DOI: 10.1111/dom.14906
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring metrics (Mean Glucose, time above range and time in range) are superior to glycated haemoglobin for assessment of therapeutic efficacy

Abstract: Aim To evaluate continuous glucose monitoring (CGM) metrics for use as alternatives to glycated haemoglobin (HbA1c) to evaluate therapeutic efficacy. Methods We re‐analysed correlations among CGM metrics from studies involving 545 people with type 1 diabetes (T1D), 5910 people with type 2 diabetes (T2D) and 98 people with T1D during pregnancy and the postpartum period. Results Three CGM metrics, interstitial fluid Mean Glucose level, proportion of time above range (%TAR) and proportion of time in range (%TIR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Additionally, TAR is a useful measure for re‐evaluation of the treatment plan and insulin dose adjustments. Recently, Rodbard et al argued that TAR may allow a better assessment of therapeutic efficacy compared with TIR or HbA1c 28 . In the present study, we found that GRI can provide a comparable value to TIR, TAR or HbA1c in risk discrimination for DR. Our findings suggest that GRI has the potential to be a valuable research endpoint or clinical measure.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Additionally, TAR is a useful measure for re‐evaluation of the treatment plan and insulin dose adjustments. Recently, Rodbard et al argued that TAR may allow a better assessment of therapeutic efficacy compared with TIR or HbA1c 28 . In the present study, we found that GRI can provide a comparable value to TIR, TAR or HbA1c in risk discrimination for DR. Our findings suggest that GRI has the potential to be a valuable research endpoint or clinical measure.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, we compared the predictive value for incident DR between GRI and other glycaemic metrics including TIR, TAR and HbA1c. As evidence has accumulated supporting the associations of TIR with the risk of numerous diabetes-related outcomes, [8][9][10][11][12][13][26][27][28] TIR has been advocated as a key CGM metric. With regard to DR, from our previous analysis of cross-sectional data from 3262 patients with type 2 diabetes, we observed that TIR obtained from 3-day CGM data is related to varying degrees of DR. 14 Furthermore, in a post hoc analysis of the seven-point self-monitored blood glucose data from the Diabetes Control and Complications Trial, TIR was also found to be strongly associated with the risk of retinopathy progression in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to TIR and hyperglycemia indices (such as TAR >180 , TAR >250 , and HyperCompo), the present study showed that mean SG was not significantly associated with the severity of WMLs. Although mean SG has been reported to be highly correlated with TAR,22 44 both hyperglycemia and hypoglycemia affect mean SG and HbA1c levels 45. This study showed that there was no association between hypoglycemic indices and the severity of WMLs unlike hyperglycemia indices.…”
Section: Discussionmentioning
confidence: 50%
“…Use of CGM metrics has been shown to be superior to glycated hemoglobin (HbA1c) for assessment of therapeutic efficacy. 3 However, because many individuals using CGM are often making critical decisions for insulin adjustments and detection of immediate or impending risk for acute glycemic events, it is important that they know they can rely on the accuracy of their glucose data. 4 Continuous glucose monitoring data have been used to also identify glucotypes to make diagnoses of atypical forms of diabetes.…”
Section: Introductionmentioning
confidence: 99%